Nilai-Nilai Sosial di Dalam Pendidikan Pemuda Perspektif Sa’id bin Ali bin Wahf Al Qahthani (Telaah Kitab Al Hadyu An Nabawi fi Tarbiyah al Aulad fi Dhau Al-Kitab Wa As-Sunnah) - Hanif Fitrianto; Junanah (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
The young generation has contributed to achieve the glory of a nation, even history has recorded youth figures who were becoming key persons in achieving that glory. Provising young generation education contained social values, especially related to national culture, is urgently needed in order prevent them from cultures those can damage national identity. Today the young generation are being influenced by a destructive culture which has an impact on their identities and impacts on social life. Instilling social values is needed to re-connect youth with society. Sa'id bin Ali bin Wahf Al-Qahthani, a muslim educator in the Middle East has written hundreds of books related to Islamic teachings, one of these books entitled by Al Hadyu An Nabawi fi Tarbiyah al Aulad fi Dhau Al-Kitab Wa As-Sunnah as a guide in Islamic education including youth. With the formulation of the problem, what are the social values contained in youth education on the perspective of Sa'id bin Ali bin Wahf Al-Qahthani? Using qualitative research through literature study and analysis with content analysis it was concluded that youth education on the perspective of Sa'id bin Ali bin Wahf Al Qahthani contains social values in the form of; caring, kindship, mutual help, empathy, justice, cooperation, and democracy.